1985
DOI: 10.1079/bjn19850127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental zinc deficiency in guinea-pigs: clinical signs and some haematological studies

Abstract: 1. Thirty-three male, weanling guinea-pigs were divided into two groups. One group was fed on a zinc-deficient (ZnD) diet (1.25 mg Zn/kg diet) for 45 d and then divided into two subgroups: subgroup 1 continued on diet ZnD while subgroup 2 was fed on a Zn-repleted diet (100 mg Zn/kg diet) for 15 d. The second group was fed on a Zn-adequate diet (50 mg Zn/kg diet) for 60 d.2. Zn deficiency could be produced within 21 d as evidenced by clinical signs and reduction in serum Zn concentration.3. Clinical signs exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(13 reference statements)
0
10
0
1
Order By: Relevance
“…A Zn deficiency has been reported to depress the humoral and cellular immune responses in guineapigs (Gupta et al, 1985;Verma et al, 1988). Antibody titer against bovine herpesvirus-1 (IBR) 14 d following vaccination were higher for stressed steers supplemented with Zn-methionine compared with the control and steers supplemented with ZnO (Spears et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A Zn deficiency has been reported to depress the humoral and cellular immune responses in guineapigs (Gupta et al, 1985;Verma et al, 1988). Antibody titer against bovine herpesvirus-1 (IBR) 14 d following vaccination were higher for stressed steers supplemented with Zn-methionine compared with the control and steers supplemented with ZnO (Spears et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified decreases in the packed cell volume and total leukocyte count accompanied by absolute lymphocytopenia and relative neutrophilia in guinea pigs (Gupta et al 1985). Several studies have demonstrated that zinc deficiency affects vitamin A metabolism, the immune system (Smith et al 1973, Quarterman and Humphries 1979, Sanecki et al 1985 and lipid metabolism (Eder andKirchgessner 1996a,b, 1997).…”
Section: Zinc Deficiency In Animalsmentioning
confidence: 99%
“…Early investigations showed that Zn depletion reduces levels of Zn and Zn metalloenzymes in many tissues and body fluids (Hoekstra et al 1956Prasad et al 1971). More recently, it was found that Zn deficiency causes increased osmotic fragility of red blood cell membranes (Johanning et al 1990) and depression in both the humoral and cellular immune responses (Gupta et al 1985;Verma et al 1988;Spears et al 1991).…”
Section: B I O L O G I C a L A D A P T A T I O N S D U R I N G Z I N mentioning
confidence: 99%